Lactic Acid Bacteria Selection for Inoculum in Producing Sweet Corn Straw Silages - Malikah Azizah; Yantyati Widyastuti; Anja Meryandini (Jurnal Ilmu Pertanian Indonesia, 2025)
Sweet corn straw has nutritional value comparable to wheat and has the potential to be used as animal feed; however, its high crude fiber concentration reduces digestion. The purpose of this study was to assess nine lactic acid bacteria (LAB) isolates from cocoa fermentation (H 0.3, H 0.13, H 0.17, H 0.24, H 0.26, H 1.22, H 2.34, H 3.1, and H 3.3) as inoculants in silage production from corn straw. LAB identification was done using CaCO₃-clear zone tests, morphological examination, and catalase testing. Isolates H 0.13 and H 2.34 performed the best, as evidenced by low pH, significant lactic acid generation, and reduced water-soluble carbohydrates. Based on 16S rRNA gene sequencing, both were identified as Lactiplantibacillus species. Silage showed good qualities, both with and without inoculants: slightly fine to moderately coarse texture, yellowish-green hue, and sour scent. Minor fungal growth was seen in inoculated samples. The nutritional content met the Indonesian National Standard (SNI) for cow feed, with low crude fiber (13.11−13.58%) and ash level (2.72−3.36%). Fermentation quality was judged "very good," with a Fleigh value higher than 85. Finally, Lactiplantibacillus isolates H 0.13 and H 2.34 work well as inoculants for sweet corn straw silage, enhancing its nutritional and fermentative quality. Keywords: corn straw, lactic acid bacteria, silage